2007
DOI: 10.1038/nphys517
|View full text |Cite
|
Sign up to set email alerts
|

A local metallic state in globally insulating La1.24Sr1.76Mn2O7 well above the metal–insulator transition

Abstract: The distinction between metals, semiconductors and insulators depends on the behaviour of the electrons nearest the Fermi level E F , which separates the occupied from the unoccupied electron energy levels. For a metal, E F lies in the middle of a band of electronic states, whereas E F in insulators and semiconductors lies in the gap between states. The temperatureinduced transition from a metallic to an insulating state in a solid is generally connected to a vanishing of the low-energy electronic excitations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
47
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 34 publications
5
47
0
Order By: Relevance
“…Loss of spectral weight in a large energy scale has been observed in a polaronic state of the colossal magnetoresistant manganites La 2−2x Sr 1+2x Mn 2 O 7 [32][33][34][35] . In the polaronic state induced by strong electron-phonon coupling, the spectral function consists of a low-energy "zero-phonon" quasiparticle peak and a hump-like high-energy incoherent resonance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of spectral weight in a large energy scale has been observed in a polaronic state of the colossal magnetoresistant manganites La 2−2x Sr 1+2x Mn 2 O 7 [32][33][34][35] . In the polaronic state induced by strong electron-phonon coupling, the spectral function consists of a low-energy "zero-phonon" quasiparticle peak and a hump-like high-energy incoherent resonance.…”
mentioning
confidence: 99%
“…In the manganites, the incoherent branch loses its partial spectral weight over an energy range of up to 0.8 eV, which is accompanied by a disappearance of the quasiparticle peaks around the metal-insulator transition temperature. This could be associated with either loss of polaron coherence 34 or a decreased fraction of metallic regions in the scenario of phase separation 33 . Assuming that the polaronic picture could be applied to the BiS 2 system, the spectral weight of the incoherent branch, i.e.…”
mentioning
confidence: 99%
“…The immediate implication is that y c = 0.85 represents the compositional critical point below which a GP is nucleated in this system (comparable results occur with 18 O substitution, Figs 1 a2-e2, a point returned to below). The idea of a critical ratio in a phase-separated view of the manganites has been discussed recently [17], focusing principally on the thermal, not compositional, variation of this ratio. By contrast, and of immediate relevance to the present conclusion, is that analysis of previous neutron diffraction experiments [14] concluded that at this same composition the role of quenched disorder was pivotal in establishing a long-ranged phase separated state.…”
mentioning
confidence: 99%
“…In order to address the issue of a proper description of the periodic systems with strong correlation, the experimental determination of band dispersions by angleresolved photoemission spectroscopy (ARPES) has been highly required, but such data have been largely limited to low dimensional compounds [9,10,11] of limited chemical variety. For three-dimensional perovskite oxides, which have a wide variety of chemical compositions, even when bulk single crystals are available, they do not have cleavage planes required for ARPES measurements.…”
mentioning
confidence: 99%